THU0202 Pattern of radiographic damage of the hand joints in rheumatoid arthritis: a study of 193 patients. (1st June 2001) - Ines, LS; Reis, P; Santos, MJ; Alexandre, M; Silva, C; Branha, A; Figueiredo, A; Nour, D; Silva, JA Da; Malcata, A; Porto, A
Abstract : Background: Metacarpophalangeal (MCP) and proximal interphalangeal (PIP) joints of the hands are some of the most frequently involved areas in rheumatoid arthritis (RA). However, observational data suggest that differences may exist between different fingers. Objectives: To evaluate the pattern of radiographic damage of the wrists and small joints of the hands in RA patients. Methods: Cross-sectional study of 193 RA patients, fulfilling the 1987 ACR criteria (female = 168 [87%], male = 25 [13%]; mean age = 57.0 ± 11.7 years; mean disease duration = 13.4 ± 8.1 years; RF positive = 72%). They attended consecutively our hospital-based outpatient rheumatology clinic. Radiographs of the hands were obtained from all patients. Wrists, MCP, PIP and distal interphalangeal joints (DIP) were scored using Larsen's method. All radiographs were evaluated by a single reader in a blinded fashion. The intrarreader concordance rate was >0.82 for all joints. Results: Mean Larsen scores were 2.25 ± 1.54 for wrists, 1.70 ± 1.49 for MCPs, 1.29 ± 1.19 for PIPs and 0.84 ± 0.74 for DIPs. There were erosive changes in 62.7% of the wrists, 39.0% of the MCPs, 27.4% of the first finger interphalangeals, 20.8% of the PIPs and 10.3% of the DIPs. Mean scores for each joint area and for each finger are presented in the Table 1 below. Conclusion: Mean radiographic damage increases from DIPs to proximal joints up to the wrist. There are also differences of the damage of each joint area between fingers. Functional and mechanical factors may contribute to these differences.